Applying Content and Language Integrated Learning Approach in Designing Chemistry Lesson Plan for High School Students - Ha, Hoang Thu; Nguyet, Ha Minh (VNU Journal of Science: Education Research; Vol 35 No 3, 2019)
Recently, teaching - learning Science subjects in English has become an urgent need of Vietnamese Education. Although piloted in high schools for gifted students and high-qualified schools with experienced teachers and good students, teaching Science subjects in English still faces many obstacles for many reasons. Among them, finding an appropriate teaching method may be the biggest challenge. The students who are good at Science subjects often does not feel confident about English. Whilst, those who are proficient in foreign language are usually afraid of science subjects and have not yet built up speciallized vocabulary about science. In this context, teaching Science subjects using Content and Language Integrated Learning (CLIL) approach shows high application potential due to the ability to balance both factors - Science knowledge and English simultaneously in a lesson. This study introduces the characteristics of CLIL approach and proposes the steps for preparing CLIL lesson plan. Also included is the analysis of the results of the Pedagogical experiment in High school of Education and Science.